(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The main aim of this study is to evaluate the impact of three independent variables viz age (A), experience of online shopping(B) and gender (C) of the online shoppers and their various interactions on customer satisfaction in online shopping. The data for the study was collected from 685 online shoppers from Vidarbha region, M.S., India through a well-structured questionnaire. The proposed relationship was investigated empirically by performing three-way ANOVA. Analysis was done using Statistical Package for Social Sciences (SPSS). This study used availability, purposive and snowball sampling techniques for selecting the samples of online shoppers in Vidarbha. The results of three-way ANOVA analysis show that, from the three independent variables, two variables viz, age and experience of online shopping were found to be significantly affecting customer satisfaction in online shopping. However, ‘gender’ was found to be insignificant in affecting satisfaction of online shoppers. The combined interaction effect of all the three variables (A*B*C) is found to be highly significant; however, the paired interactions between A*B, A*C and B*C were found to be insignificant. Therefore, the research concludes that, age of online shoppers and experience of online shopping significantly affect their satisfaction in online shopping. The online shoppers in the age group of 29 to 48 years found to be most satisfied. The online shoppers having experience more than 4 years of online shopping found to be most satisfied; and both male and female online shoppers found to be equally satisfied with the online retailers.